Traces in and out: a deconstructionist reading of English translations of Jacques Prevert's Paroles (1946/7) - Malabo, Diane (My University, 2010)
Abstract This study is a comparative analysis of selected poems from Jacques Prévert’s Paroles (1946/1947). It is an application of a mainstreamed theoretical paradigm comprising deconstruction, hermeneutics and relevance. The overall aim is to show how each translator of Jacques Prévert derived latent and relatively obvious semantic possibilities from the ST. This objective is attained through a descriptive analysis of the translation process, and an attempt to interpret the findings thereby revealed, primarily according to the tenets of deconstruction, and according to the tenets of hermeneutics and relevance if possible. The theoretical model that grounds the study is a non-reductionist, non-prescriptivist and non-evaluative. That is the reason why the traditional terminology associated with some of the theoretical aspects mainstreamed in the model have been adapted to fit in with the general aim of the study. Actual reading experiences hardly entail a consecutive reading of more than one text. But this research is like a laboratory experiment; it tests the applicability of integrated [theoretical] formulae to a hypothetical case, the consecutive reading of selected poems from Paroles (1946/1947) and their English translations.
Keywords: a priori; difference; differance; deconstruction; semantic multiplicity; interpretation; clues; post modern theory; text analysis; texts' afterlives; trace